Biomes - Buckey, A. W. (Abdo Reference, 2024)
This title introduces readers to the major types of biomes. Alongside climate, readers will learn about the plants and animals that call each biome home and how they interact with their environment. Features include a glossary, additional resources, and an index. Aligned to Common Core Standards and correlated to state standards.